Inaccuracy Analysis of Diagnosis Code of Disease in Medical Records with SIMPUS at Purwoharjo Public Health Center - Ida Nurmawati; Sulandari Sulandari; Ervina Rachmawati; Dony Setiawan; Kurniawan Erman Wicaksono; Ikha Nurjihan (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2024)
The inaccuracy of the disease diagnosis code is one of the problem affecting the quality of health services. Based on the preliminary result, 89 outpatient diagnosis codes in a medical record found 30 inaccuracies data from SIMPUS result of general poly at Purwoharjo Health Center. The impact of this inaccuracy has been influenced by the accuracy of disease data that resulted from making report data. The purpose of this study was to analyze the inaccuracy of disease diagnosis codes for outpatient medical records with SIMPUS at Purwoharjo Public Health Center. It was a descriptive study with observation, interviews, and documentation data collection. The object of this study was 95 outpatient medical records with simple random sampling. The result of this research was found 42% inaccuracy code of outpatient medical records with SIMPUS. The cause of these problems was the coder less careful in enforcing the disease diagnosis code because of the high workload of the coder and there’s no job description in SOP, so the advice that can be given to Purwoharo Health Center is to hold a division of tasks evenly and can be written in the SOP job description.